Strain rate effect on interfacial bond behaviour between BFRP sheets and steel fibre reinforced concrete - Yuan, C.; Chen, Wensu; Pham, Thong; Hao, Hong; Jian, C.; Shi, Y. (ELSEVIER SCI LTD, 2019)
Numerous studies have shown that using steel fibre reinforced concrete (SFRC) and retrofitting with Fibre-reinforced polymer (FRP) composites can improve the strength and ductility of RC structures against impact and explosive loadings. The interface between FRP and concrete has been identified as one of the weakest parts of the FRP strengthened structures subjected to dynamic loading, with debonding failure usually observed as the primary failure mode. In order to properly analysis and design of FRP strengthened reinforced concrete (RC) structures, it is important to understand the dynamic bonding strength between FRP and concrete. An experimental investigation regarding to the dynamic interfacial bond behaviour between basalt fibre (BFRP) sheets and SFRC is carried out in this study. Concrete prisms were made of short steel fibres with three volumetric fractions (i.e. Vf = 0.5%, 1.0%, and 1.5%) to improve the tensile strengths. To achieve different strain rates, the loading velocities varied from 8.33E-6 m/s, 0.1 m/s, 1 m/s, 3 m/s, to 8 m/s. Experimental results show the bond strength and bond-slip were sensitive to strain rate. The loading rate changed the debonding failure modes from concrete substrate failure to interfacial debonding. In addition, the shear resistance of the interface increased with the fibre volume under both quasi-static and dynamic loadings. Based on the testing data, an empirical bond-slip model, incorporating the volumetric fraction of steel fibre and strain rate, is established for FRP-strengthened SFRC structures.